PD-1 inhibitor treatment in a penile cancer patient with MMR/MSI status heterogeneity: A case report - YunYi Du; XiaoLing Zhang; Ying Zhang; WeiLing Li; WenQing Hu; Liang Zong; Jun Zhao (Taylor & Francis Group, 2022)
Penile cancer is a rare malignant disease. Paclitaxel combined with platinum is often used as a first-line chemotherapeutic regimen for late-stage penile cancer, and there is no standard second-line treatment. Clinical trials of immunotherapy for penile cancer are ongoing. There are no reports on PD1 inhibitor treatment in metastatic penile carcinoma patients with MMR/MSI status heterogeneity. A 68-year-old patient was hospitalized with bilateral inguinal lymph node metastasis and local penile recurrence after penile cancer surgery. The lesion of the right inguinal lymph node showed a mismatch-repair-deficient (dMMR)/microsatellite instability-low (MSI-L) status. After 3 cycles of sintilimab (a PD1 inhibitor) combined with paclitaxel and cisplatin, the partial response of the tumor was evaluated. Subsequently, sintilimab monotherapy was used as maintenance treatment for 2 months. However, The lesion of local penile recurrence showed mismatch repair proficient (pMMR)/microsatellite stability (MSS) status by secondary biopsy when progressed rapidly. Interestingly, after continued treatment with sintilimab combined with gemcitabine, the patient achieved a partial response again. We should be aware of the importance of secondary biopsy for different lesions to confirm the heterogeneity of MMR/MSI status. For penile cancer patients with MMR/MSI status heterogeneity, PD1 inhibitors combined with chemotherapy are safe and effective. Due to oligometastatic lesion progression caused only by the heterogeneity of MMR/MSI status, PD1 inhibitor cross-line therapy can also be considered an appropriate treatment.